النيابة والتضمين في معاني حروف الجر - Danial Jamal (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2017)
Knowing the structure of Arabic and returning to it is able to save us from mistakes in using the Arabic language. Because Arabic has many advantages that other languages in the world, among them are rich and very detailed linguistic structures and laws, so that Arabic is a pure language, not mixed with other languages. With the structure and language law is also Arabic language is still maintained until today. Therefore, this study aims to discuss the structure of Arabic language that examines the meaning of the huruf jar, in which the meanings of the huruf jar are almost innumerable, while the huruf jar is very limited and few in number.